Relationship between lifting load and shoulder pain complaints in material transport workers - I Putu Meika Semara Putra; Ni Luh Putu Gita Karunia Saraswati; I Putu Adiartha Griadhi; Anak Ayu Nyoman Trisna Narta Dewi (Physical Therapy Journal of Indonesia, 2023)
Background: Many workers have experienced increased shoulder pain due to lifting and transporting materials. Workers who lift too heavy a load can cause unhealthy body conditions and experience pain complaints in the shoulder area. This study aimed to determine the relationship between lifting weights and shoulder pain complaints of material transport workers in Gianyar. Methods: This research used the cross-sectional design. The research was conducted offline or directly in the field. The sampling technique used is using total sampling with a total of 64 people. The Spearman rho test was used to analyze the data. Results: The research results on lifting weights with shoulder pain were obtained from research samples with complaints of shoulder pain. Namely, there were 62 people, 99% without complaints of shoulder pain, as much as 1%. Through the Spearman test, the pain value p = 0.000, and the r-value in the relationship of shoulder pain complaints is r = 0.551. Conclusion: There was a relationship between lifting weights and shoulder pain complaints in material transport workers in Gianyar.